2021
DOI: 10.1007/s10649-021-10060-1
|View full text |Cite
|
Sign up to set email alerts
|

Are we all in this together?: mathematics teachers’ perspectives on equity in remote instruction during pandemic

Abstract: The COVID-19 pandemic is an unprecedented situation that influenced all aspects of society, including education. Millions of students found themselves adjusting to a new medium of mathematics instruction, not to mention the teachers who had to provide instruction through remote sources. Considering students’ diverse social, economic, and academic background, this study sought to examine teachers’ perspectives on factors that support or hinder how equity is attended to in mathematics during remote instruction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…From diverse perspectives, a plethora of studies have examined the impact of COVID-19 lockdown on home education ( Cahoon et al, 2021 ), social life and mental health of students ( Chaturvedi et al, 2021 ) competences of parents, children, and teachers ( Öçal et al, 2021 ), and student academic performance ( Iglesias-Pradas et al, 2021 ). With face-to-face teaching replaced by remote instruction, new approaches to curriculum design ( Yilmaz et al, 2021 ), OT activity design and implementation ( Wu, 2021 ), and teachers’ technology acceptance ( Hong et al, 2021 ) have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…From diverse perspectives, a plethora of studies have examined the impact of COVID-19 lockdown on home education ( Cahoon et al, 2021 ), social life and mental health of students ( Chaturvedi et al, 2021 ) competences of parents, children, and teachers ( Öçal et al, 2021 ), and student academic performance ( Iglesias-Pradas et al, 2021 ). With face-to-face teaching replaced by remote instruction, new approaches to curriculum design ( Yilmaz et al, 2021 ), OT activity design and implementation ( Wu, 2021 ), and teachers’ technology acceptance ( Hong et al, 2021 ) have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This study presented various ways to address the challenges in online teaching as literature indicated (Aldon et al, 2021 ; Cao et al, 2021 ; Chirinda et al, 2021 ; Kalogeropoulos et al, 2021 ; Mailizar et al, 2020 ; Yılmaz et al, 2021 ). Specifically in this study, we found the following: (1) Limited ‘face-to-face’ communication online is still a pressing technological constraint.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified the difficulties and challenges in online teaching and learning in response to the emergency of the pandemic (Aldon et al, 2021 ; Cao et al, 2021 ; Chirinda et al, 2021 ; Clark-Wilson et al, 2020 ; Engelbrecht et al, 2020 ; Kalogeropoulos et al, 2021 ; Mailizar et al, 2020 ; Yılmaz et al, 2021 ). Teachers encounter challenges in four areas: technology, students, mathematics, and resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 2 years, many scholars have analyzed the pandemic situation from many points of view. Among them, many have studied the conditions of students and teachers from a teaching, social and psychological point of view (e.g., Borba, 2021;Cassibba et al, 2021;Yilmaz et al, 2021). Bakker et al (2021) wondered if the pandemic changed the perspectives on the themes like mathematics education research.…”
Section: Distance Learningmentioning
confidence: 99%